Treatment of Anxiety Disorders and Comorbid Alcohol Abuse with Buspirone in a Patient with Antidepressant-Induced Platelet Dysfunction: A Case Report - Mir Mazhar; Tariq Hassan; Tariq Munshi (Case Reports in Psychiatry)
The risk of abnormal bleeding with serotonin reuptake inhibitors has been known, but there is insufficient evidence base to guide pharmacological treatment of anxiety in patients with underlying haematological conditions. The following case report is about a 50-year-old female with generalized anxiety disorder, social phobia, obsessive compulsive disorder, and alcohol abuse where pharmacological treatment of anxiety symptoms has been difficult as it would lead to bruising due to the patient’s underlying qualitative platelet dysfunction. Treatment with venlafaxine, citalopram, escitalopram, and clomipramine resulted in improvement and anxiety symptoms, as well as reduction in alcohol use, but pharmacological treatment has to be discontinued because of bruising and hematomas. In view of an active substance use disorder, benzodiazepines were avoided as a treatment option. The patient’s anxiety symptoms and comorbid alcohol abuse responded well to pharmacological treatment with buspirone which gradually titrated up to a dose of 30 mg BID. Patient was followed for around a six-month period while she was on buspirone before being discharged to family doctor’s care. Buspirone is unlikely to have a significant effect on platelet serotonin transponder and could be an effective alternative for pharmacological treatment of anxiety in patients with a bleeding diathesis.